Drug-Drug Interaction Potential, Cytotoxicity, and Reactive Oxygen Species Production of Salix Cortex Extracts Using Human Hepatocyte-Like HepaRG Cells - Gomes, João Victor Dutra; Herz, Corinna; Helmig, Simone; Förster, Nadja; Mewis, Inga; Lamy, Evelyn (Frontiers in Pharmacology, 2021)
Herbal preparations of willow bark (Salix cortex) are available in many countries as non-prescription medicines for pain and inflammation, and also as dietary supplements. Currently only little information on toxicity and drug interaction potential of the extracts is available. This study now evaluated the effects of two Salix cortex extracts on human hepatocyte-like HepaRG cells, in view of clinically relevant CYP450 enzyme activity modulation, cytotoxicity and production of reactive oxygen species (ROS). Drug metabolism via the CYP450 enzyme system is considered an important parameter for the occurrence of drug-drug interactions, which can lead to toxicity, decreased pharmacological activity, and adverse drug reactions. We evaluated two different bark extracts standardized to 10mg/mL phenolic content. Herein, extract S6 (S. pentandra, containing 8.15mg/mL total salicylates and 0.08mg/mL salicin) and extract B (industrial reference, containing 5.35 mg/mL total salicylates and 2.26mg/mL salicin) were tested. Both Salix cortex extracts showed no relevant reduction in cell viability or increase in ROS production in hepatocyte-like HepaRG cells. However, they reduced CYP1A2 and CYP3A4 enzyme activity after 48h at ≥ 25µg/mL, this was statistically significant only for S6. CYP2C19 activity inhibition (0.5h) was also observed at ≥ 25µg/mL, mRNA expression inhibition by 48h treatment with S6 at 25µg/mL. In conclusion, at higher concentrations, the tested Salix cortex extracts showed a drug interaction potential, but with different potency. Given the high prevalence of polypharmacy, particularly in the elderly with chronic pain, further systematic studies of Salix species of medical interest should be conducted in the future to more accurately determine the risk of potential drug interactions.